Factors Influencing Audit Delays With Profitability as an Intervening Variable (A Case Study of Infrastructure Sector Companies Listed on the Indonesia Stock Exchange from 2020 to 2024) (Dhana, 2026)
This study aims to empirically test the effect of liquidity, solvency, and company age on audit delay with profitability as an intervening variable (a case study of Infrastructure Sector companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period). The population of this study is Infrastructure Sector companies for the 2020-2024 period. The research sample was selected using purposive sampling, a sampling technique using predetermined criteria, resulting in a total of 125 research samples. This research method uses quantitative methods. This study uses secondary data obtained through data available on the Indonesia Stock Exchange (IDX) and the respective company websites. The results show that Liquidity has no effect on profitability.that solvency has an impact onprofitability.company age has an effect onprofitability.that liquidity has an impact onaudit delay.solvency does not affectaudit delay.company age has an effect onaudit delay.profitability has an impact onaudit delay.liquidity has no effect onaudit delay through profitability.solvency does not affectaudit delay through profitability.company age does not affectaudit delay through profitability